Characterising non-tariff trade policy - Julia Grübler; Oliver Reiter (The Vienna Institute for International Economic Studies (wiiw), 2020)
Starting in the 1960s with the Kennedy Round of the General Agreement on Tariffs and Trade (GATT), nontariff measures (NTMs) have been replacing tariffs continuously as the core element of trade negotiations. Today they take centre stage in all EU trade agreements with industrialised and emerging economies. By matching product codes to the rich data of NTM notifications to the World Trade Organization and complementary information provided by the Temporary Trade Barriers Database, we provide a valuable open data source for trade policy analysis. Using data for 148 NTM-imposing economies for the period 1995-2019, we describe the evolution of different types of NTMs along countries and sectors, with a special focus on NTMs implemented by the EU. The analysis of our data, paired with comparisons with other sources, shows the merits and shortcomings of the WTO's service in providing transparency over members' trade policies.
https://wiiw.ac.at/wiiw-ntm-data-ds-2.html
Keywords: F13; F14; F68; O24; 330; non-tariff measures; trade policy; trade barriers; database; open data; WTO; I-TIP; TTBD